Quality infrastructure and natural disaster resiliency - Farhad Taghizadeh-Hesary; Naoyuki Yoshino; Aline Mortha; Tapan Sarker (Asian Development Bank Institute (ADBI), 2019)
A review of the academic literature on the topic has proved that most studies have been focused on how to finance the risk and indemnify the damages caused by an earthquake, rather than on mitigation measures. This study assessed the impact of quality infrastructure, development indicators and corruption on damages caused by a natural disaster using a panel data from 14 Asia and Pacific countries for 2007-2017. Using the generalized method of moments and vector error correction model, the study quantified the role of quality infrastructure in disaster impact mitigation. The empirical results suggest that increasing the quality of infrastructure may have a large impact on decreasing costs arising from natural disasters, and that policy makers should use public-private cooperation and schemes introduced by the study to prompt the construction of quality infrastructure. Because quality infrastructure development suffers from a lack of financing, several financing schemes are presented.
Keywords: Q54; H54; O18; H84; 330; disaster resiliency; disaster risk financing; quality infrastructure; disaster risk management